Embedding mental wellbeing in the curriculum: a collaborative definition and suite of examples in practice - Lister, Kate; Allman, Zoë (Frontiers in Education, 2024)
The sector-wide challenge of student mental wellbeing within Higher Education (HE) requires universities to systematically and holistically enhance their practice and approaches. This paper recounts how an interdisciplinary team of academics, senior leaders, professional services and Students' Union representatives across seven institutions responded to this need by collaboratively identifying definitions, good-practice for replication, and benefits of activity to embed mental wellbeing in the curriculum. Considering and exploring definitions across HE, our study provides clarity and reference points for definitions, particularly around the nature of 'embedding' in relation to mental wellbeing for students. Five core themes for mental wellbeing in HE were identified and defined through this study: flourishing or thriving, balance, community and belonging, dynamic, and inclusive. Furthermore, a five-point definition of embeddedness developed; it being modelled in practice, tailored to needs, inherent in values, ethos and culture, a holistic partnership approach, and represented in strategy supported by appropriate resource. These are represented as a Mental Wellbeing Embeddedness Framework. The study sought good-practice examples from across seven HE providers, presented as example resources for replication by others in the sector seeking to address similar challenges within their institutions. Twenty-seven examples were developed into an online Open Educational Resource toolkit, providing clear examples for use in a range of settings and responding to different needs around student mental wellbeing. Each example sharing its original rationale for development and clear list of benefits to be seen from replicating the initiative. Sector feedback to date indicates referencing the definitions activity and expanding this for use in other contexts, replication of good-practice examples in different settings, and support for identification of the benefits that can be achieved from embedding mental wellbeing in the 2 This is a provisional file, not the final typeset article curriculum. This paper is a call to action, shaping the future direction of student mental wellbeing, supported by policy, practice, and constant innovation.